Private-public partnerships for expanding broadband access: Lessons from the Cintur\~ao Digital do Ceará Network in Brazil - Fernando Carvalho; Flavio Feferman; Peter Knight; Glenn Woroch (International Telecommunications Society (ITS), 2014)
The Cintur\~ao Digital do Ceará (CDC) is a pioneering infrastructure project that delivers broadband access to large cities, small towns and rural areas throughout the State of Ceará in northeast Brazil. The CDC was built and operated using a unique business model that innovates on the standard public-private partnership (PPP) - an increasingly popular means to undertake Information Communications Technology (ICT) deployments. We review the technical, legal and organizational features of the CDC project with a focus on how they were designed to cope with the unique economic and political conditions of the region. It is particularly instructive how the CDC business model evolved over time in response to political challenges and market failures. We highlight how the model can be adapted to other regions within Brazil, as well as to other developing countries, that seek to pursue dual goals of financial sustainability expansion of broadband access to underserved populations.
Keywords: 330